Analisis Faktor-Faktor Yang Memengaruhi Perkembangan Embrio Ikan Nilem (Osteochilus Vittatus Valenciennes, 1842) - Silvani Yuan Tamu Ina; Sartika Tangguda; Ni Putu Dian Kusuma (JURNAL RISET RUMPUN ILMU HEWANI, 2023)
Knowledge related to Bonylip Barb (Osteochilus vittatus Valenciennes, 1842) embryo development is essential as a first step to developing a suitable fish hatchery method to support higher egg quality and quantity, thus increasing fry production. The purpose of the observation is to study and provide information on the development of bonylip barb fish embryos, which has been limited to academics and the public until now. Observations were carried out in April 2023 at the Muntilan Fish Health and Environmental Testing Laboratory, Central Java. Bonylip Barb embryo development takes 23 hours and 11 minutes after fertilization. This process is influenced by factors that limit the embryo's development until hatching.